The Marketing Audit : Translating marketing theory into practice - McDonald, Malcolm, author 414975; Leppard, John W., author 635028 (Oxford ; Boston : Butterworth-Heinemann, 1991)
Understanding the marketing process; the marketing planning process - the main steps; removing the barriers to marketing planning; the customer and market audit; the product audit; setting marketing objectives and strategies; advertising and sales promotions; the sales plan; the pricing plan; the distribution plan; marketing information, forecasting and organizing for marketing; implementing the marketing plan; quick checklist and the marketing MoT, SWOT analysis; the strategic marketing plan.